PENGARUH PENYUSUNAN POLARISASI PADA SISTEM ANTENA MIMO TERHADAP KAPASITAS KANAL - Abdurrahman Rizki; Alloysius Adya Pramudita; Trasma Yunita (TEKTRIKA, 2020)
Multiple Input Multiple Output (MIMO) system is a technology that has the potential to be developed to increase channel capacity. The increase in channel capacity in the MIMO system is not only determined by the number of antennas, but is determined by the characteristics and arrangement of the antenna concept. This study identifies the effect of circular polarization on the MIMO antenna system on channel capacity. Co-polarization consists of a Left Hand Circular Polarization (LHCP) and Right Hand Circular Polarization (RHCP) configuration, while cross-polarization consists of an RHCP-LHCP configuration. The co-polarization of the antenna with the LHCP configuration results in an estimated channel capacity of 11,578 bps / Hz when it is at the lowest Signal to Noise Ratio (SNR) is 5 dB